PENGARUH KUALITAS PELAYANAN DAN KINERJA KARYAWAN TERHADAP KEPUASAN MAHASISWA PADA UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARI BANJARMASIN (Studi Kasus pada Kegiatan Penerimaan Mahasiswa Baru) - Siti Mardah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
This study aims to determine how much influence the quality of service and employee performance has on student satisfaction at the Islamic University of Kalimantan Muhammad Arsyad Al Banjari, especially in the New Student Admissions Counter for the 2019-2020 period. This study uses a sample size of 98 respondents using the slovin formula. . From this research, it is concluded that the variable X1 has a positive and insignificant effect on Variable Y, so that H1 is rejected and for Variable X2 the results have a positive and significant effect on Variable Y, so that H2 is accepted. For the F test, the significance value is 0.000 <0.005 and the F value is calculated. 12.978>3.09. So it can be concluded that H3 is accepted. The value of R Square is 0.472, meaning that the simultaneous influence of variables X1 and X2 on variable Y is 47.2%, and the remaining 52.8% is influenced by other variables outside the variable. that the author tested.